Bioactive Compounds Offered in Microcapsules to Determine the Nutritional Value of Copepods’ Natural Diet - Dörthe C. Müller-Navarra; Mark E. Huntley (Marine Drugs, 2013)
Experiments were performed, feeding Calanus pacificus seston and a food consisting of seston and microcapsules (μ-caps), i.e., protein and lipid μ-caps to test for potential biochemical limitation. Seston was collected off Scripps Pier (La Jolla, CA, USA). Whereas protein μ-caps were too small to be efficiently ingested, lipid μ-caps rich in ω3-highly-unsaturated fatty acids (ω3-HUFA) were ingested similarly to natural seston and lipids were assimilated. However, egg production experiments exhibited that animals fed with lipid μ-caps didn’t produce significantly more eggs than with seston of equal carbon concentration and egg production even declined when the diet consisted of 50% lipid μ-caps. Thus, the content of certain ω3-HUFA seemed to have been sufficiently high in seston to prevent limitation. Algal counts revealed that seston consisted mainly of plankton rich in those fatty acids, such as cryptophytes, dinoflagellates, diatoms, and ciliates in the edible size range. This might be characteristic for upwelling systems like the area off Southern California which are known for high trophic transfer efficiency.